Explorando o potencial da combinação de cinemática e EMG para melhorar a identificação de indivíduos com dor subacromial no ombro - Freire, Lucas Cruz (2024)
Introduction: Around 16% of the population is affected by musculoskeletal diseases involving the cingulum of the upper limb; Approximately about 44% to 65% of affected individuals experience subacromial shoulder pain (SDS). Kinematic changes and electromyographic (EMG) activity in the shoulder joint complex have been described, however, there is no consensus in the literature regarding the changes in individuals with SDS. Objective: To compare the angular kinematics (CIN) and electromyographic (EMG) activity of the scapula, trunk and arm during shoulder flexion-extension and abduction-adduction movements of individuals with SDS and a control group, using the Movement Deviation Profile (MDP ) a self-organizing neural network, comparing isolated and unified CIN and EMG variables. Methods: This is a cross-sectional study, with a sample of one hundred and sixteen participants (41 men and 75 women). Fifty-six had SDS (age: 26.9±7.02 years, height: 166.8±7.96 m and BMI: 24.4±3.53 kg/m2) and 60 had no pain (age: 22.3 ±3.03 years, height: 166.5±837 m and BMI: 23.6±2.96 kg/m2). The three-dimensional kinematics of the angles in the frontal, sagittal and transverse planes of the scapula, trunk and arm were analyzed. As well as the analysis of surface electromyography of the acromial, clavicular and spinal deltoid muscles, ascending, transverse and descending trapezius, serratus anterior and biceps brachii, where the signals were filtered, rectified and smoothed. The task involved shoulder flexion/extension and abduction/adduction movements starting from the anatomical position until reaching the maximum range of motion, in each plane and returning to the initial position at a self-selected speed. MDP was used to analyze kinematics and EMG separately and then combined. The mean MDP Z-score was calculated to compare normalized results between individuals with and without SDS. A multivariate analysis with Bonferroni post-hoc test compared the groups considering p < 0.05. Results: There was an interaction between the two groups during flexion/extension (λ=0.844, F=6.885, P<0.0001) and abduction/adduction (λ=0.917, F=3.396, P<0.02). There was a difference in kinematics and kinematics with EMG in flexion/extension and only in kinematics in abduction/adduction. Conclusion: The MDP was able to differentiate individuals with SDS and those without pain, with the variable that most differentiated the groups being the kinematics during the arm flexion/extension movement.